Understanding donation frequency: insights from current plasma donors. Issue 2 (17th December 2019) - Thorpe, Rachel; Masser, Barbara M.; Nguyen, Lilly; Davison, Tanya E.
Abstract : Background and Objectives: Encouraging existing plasma donors to donate more frequently is a key objective for blood donation services committed to expanding yield through voluntary non‐remunerated plasmapheresis donation. This requires an understanding of donors' perspectives on their current donation practice and how this relates to their knowledge and beliefs about the need for plasma. To explore this, Australian plasma donors were interviewed about how they arrived at the frequency at which they donate. Materials and Methods: Semi‐structured telephone interviews were conducted with 105 Australian plasmapheresis donors. Results: Key themes identified were as follows: fitting donation into busy lives and how ideas about being an ongoing donor and the institutional context shaped their perspective on frequency; perceptions of the impact of donation on health; and wanting to make a greater contribution. Conclusion: Experienced plasma donors work to maintain a donation practice in the context of busy lives often by adopting a flexible approach to donation frequency. Their knowledge of the contribution their donations make is key to their continued donation, yet most identified constraints to donating more frequently. Health concerns were a particular concern for some, and more research is needed to understand donors' perspectives on the impact of donating on their health.